"Myth of a Poet" by Anna Akhmatova in the Context of European Literature: Intertextual Analysis - Mikhailova, Galina P. (Respectus Philologicus, 2003)
The article is based on the idea of Anna Akhmatova’s poetry as a text where an open or hidden citation is the basic element. The parallels between poetry of Anna Akhmatova and European poets can be found and justified in intertextual way. The article is concerned with the relationships between the verses from "Poem Without a Hero" by Akhmatova and several texts by R. Browning, P. B. Shelley, G. N. G. Byron, and Th. Gautier. Several European texts being within Akhmatova’s verses create a text, which has a more complicated meaning. Akhmatova’s "Myth of a Poet" is closely related to Nikolay Gumilev’s personality and poetry.